Content for the Formation of Concepts About Environmental Protection in Students - Abdirasulov Lochinbek Khusniddinovich (Genius Publishing Group, 2023)
The article presents information about the content and importance of forming a positive attitude to nature among students based on the formation of ecological culture and ecological outlook
Keywords: Ecology; environment; atmosphere; enterprise; nature